Structure‐Activity Relationship of Hetarylpropylguanidines Aiming at the Development of Selective Histamine Receptor Ligands†. Issue 3 (5th March 2019) - Pockes, Steffen; Wifling, David; Buschauer, Armin; Elz, Sigurd
Abstract: New classes of alkylated hetarylpropylguanidines with different functionality and variation in spacer length were synthesized to determine their behavior at the four histamine receptor (H1 R, H2 R, H3 R, H4 R) subtypes. Alkylated guanidines with different terminal functional groups and varied basicity, like amine, guanidine and urea were developed, based on the lead structure SK&F 91486 (2 ). Furthermore, heteroatomic exchange at the guanidine structure of2 led to simple analogues of the lead compound. Radioassays at all histamine receptor subtypes were accomplished, as well as organ bath studies at the guinea pig ( gp ) ileum ( gp H1 R) and right atrium ( gp H2 R). Ligands with terminal functionalization led to, partially, highly affine and potent structures (two digit nanomolar), which showed up a bad selectivity profile within the histamine receptor family. While the benzoylurea derivative144 demonstrated a preference towards the human ( h ) H3 R, S‐methylisothiourea analogue143 obtained high affinity at the h H4 R (pKi =8.14) with moderate selectivity. The molecular basis of the latter finding was supported by computational studies. Abstract : Selectivity first ! Structure‐activity relationship of 27 new ligands from the hetarylpropylguanidine‐type was investigated at the four histamine receptor subtypes with detailed pharmacological characterization. Methylisothiourea analogue143 turned out to have high affinity at the h H4 R with perceptible selectivity. Computational studies for143 at both h H4 R and h H3 R were accomplished in order to gain more insight into the respective binding modes.